Clinical effectiveness of four neuraminidase inhibitors (oseltamivir, zanamivir, laninamivir, and peramivir) for children with influenza A and B in the 2014–2015 to 2016–2017 influenza seasons in Japan. Issue 6 (June 2018) - Ishiguro, Nobuhisa; Koseki, Naoko; Kaiho, Miki; Ariga, Tadashi; Kikuta, Hideaki; Oba, Koji; Togashi, Takehiro; Morita, Keisuke; Inagawa, Akira; Okamura, Akiko; Yamazaki, Shigeru; Shida, Satoru; et al.
Abstract: The clinical effectiveness of four neuraminidase inhibitors (NAIs) (oseltamivir, zanamivir, laninamivir, and peramivir) for children aged 0 months to 18 years with influenza A and B were investigated in the 2014–2015 to 2016–2017 influenza seasons in Japan. A total of 1207 patients (747 with influenza A and 460 with influenza B) were enrolled. The Cox proportional-hazards model using all of the patients showed that the duration of fever after administration of the first dose of the NAI was shorter in older patients (hazard ratio = 1.06 per 1 year of age, p < 0.001) and that the duration of fever after administration of the first dose of the NAI was shorter in patients with influenza A infection than in patients with influenza B infection (hazard ratio = 2.21, p < 0.001). A logistic regression model showed that the number of biphasic fever episodes was 2.99-times greater for influenza B-infected patients than for influenza A-infected patients ( p < 0.001). The number of biphasic fever episodes in influenza A- or B-infected patients aged 0–4 years was 2.89-times greater than that in patients aged 10–18 years ( p = 0.010), and the number of episodes in influenza A- or B-infected patients aged 5–9 years was 2.13-times greater than that in patients aged 10–18 years ( p = 0.012).